Implementasi Media Pembelajaran Berbasis Game Edukasi dalam Mata Pelajaran PPKn di SMP Negeri 1 Gondang - Purnamasari, Nurna Listya; Rahmawati, Ida (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to explore the implementation of educational gamebased learning media in the subject of Pancasila and Civic Education (PPKn) at SMP Negeri 1 Gondang. The research is motivated by the low learning interest among students toward PPKn, which is often perceived as unengaging and overly theoretical, as well as the limited use of interactive learning media in schools. Educational games such as Wordwall and Canva were selected as alternative tools to create a more dynamic and enjoyable learning experience. This research employed a qualitative approach with a descriptive design. Data collection techniques included direct observation, in-depth interviews, and documentation studies. The research subjects were a PPKn teacher and ten students from class VIII A. The findings indicate that the use of educational games positively contributes to increasing students' interest in learning, facilitating better understanding of the subject matter, and encouraging active participation in the learning process. Teachers also found the media beneficial, as it allowed for more varied and engaging content delivery. However, the implementation still faces challenges such as limited access to technological devices and uneven internet connectivity. Therefore, support from the school is needed in terms of infrastructure provision and teacher training to optimize the use of digital media in the learning process.